(untitled) (Teacher’s World: Journal of Education and Research, 2023)
Due to the global pandemic, there has been an emergency shift in higher education of Bangladesh from face-to-face to fully online mode. This quick and somewhat unplanned change in the mode of teaching-learning has created a lot of challenges for both the teachers and the students. It is evident that the students, especially the public university students are mostly suffering because of this change. This qualitative study thus focuses on the perceptions of the students of University of Dhaka about this new way of teaching and learning and its effects on their lives. The finding reveals that most of the challenges are regarding infrastructural conditions, economic condition, mental wellbeing and teacher-student relationship. This study also explores possible solutions for these challenges and ways to incorporate online or blended education strategies in the higher education system of Bangladesh. Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.41-53